A notícia na era da devoração da imagem - Nascimento, Marco Antonio Camargo (2016)
Since the end of 2010, news programs have no longer been watched as they used to be. TV is in real time on the Internet, computers, laptops, tablets and mobile phones. In the era of digital convergence, viewers do not only watch TV, but they concomitantly access the content from live images or on demand. This work aims to analyze the codes of this image culture since the beginning of television in Brazil and to analyze the changes undergone by the advent of social media. It also intends to point out the affinity between the nature of the accelerated images and which are out of control of this online media generation with the nature of the images portrayed by the German thinker Aby Warburg. The research corpus comprises an image cut of the period in which the media revolution has resulted in a new language. The hypothesis is that TV, almost seven decades later, must be understood as a broadcasting language, from which it originated, and as a new product of media visibility resulting from the advent of social media. Television has, for the first time, lost its supremacy to the Internet and needed to establish new patterns of relationship with viewers. The work aims to demonstrate the phenomenon of this change and it is based on studies and research on journalism, television and image, particularly those involving technology and thinkers on the image culture. It makes a parallel with the German thinker Aby Warburg, whose theory has characteristics of the language disseminated in the digital communication culture. The scientific research of this study allowed to conclude that TV has been in conflict with the social network as Hercules had been with Hydra. Journalism, which has the news as its major symbolic value, means tactile, volatile and shared mediation of this conflict